"I didn't Mean to…": Practical Suggestions for Understanding and Teaching Students with Sexualized Behavior. (February 2013) - Rappaport, Nancy; Minahan, Jessica
Teachers can develop a plan for dealing with students who struggle with challenging behaviors, which helps teachers respond effectively and helps students change their behavior.